Some Clinical and Inflammatory Aspects of Trichomonas vaginalis Infection among Women with Pelvic Inflammatory Diseases - Abdul Jabbar, Zainab Rasheed; Al-warid, Harith Saeed (Iraqi Journal of Science, 2021)
Infection with Trichomonas vaginalis and its relation to some diseases have lately had much attention. The objective of this study was to assess the infection rate of T. vaginalis and its relation to pelvic inflammatory diseases, infertility, and vaginosis. The study also assessed some demographic, clinical, and immunological parameters in women infected with T. vaginalis. The study included 160 non-pregnant married women who attended some private clinics and public hospitals in Baghdad from October 2020 to February 2021. All participants had symptoms of vaginal discharge only or vaginal discharge with lower abdominal pain. The participants were divided into an infertility group (n = 61) and fertility group (n = 99). The participants were also divided into Pelvic Inflammatory Disease (PID) group (n=41) and non-PID group (n=119). All participants underwent vaginal examination. Vaginal swabs were taken from all participants for T. vaginalis, bacteria, yeast, clue cell, pH, and vaginal leukocyte examinations. Sera were also taken to measure both IL-1α and IL-8 using sandwich ELISA technique to compare them with apparently healthy control subjects who had no vaginal discharge. The study revealed that the total infection rate of T. vaginalis was 14.37%. The results showed no significant relations between T. vaginalis positive status and each of age, infertility, vaginosis, contraceptive use, and high BMI. While a significant relation (P=0.03) was noticed between T. vaginalis positive status and PID. Women with PID exhibited a higher infection rate with T. vaginalis (24.39%) versus non PID women (10.92%). High clue cells number was not significantly related to T. vaginalis positive status, only if both PID and vaginosis were considered in the statistical analysis. In addition, high leukocytes count was not related to T. vaginalis positive status. While abnormal vaginal pH was significantly (P=0.01) related to T. vaginalis positive status. Finally, the levels of both IL-1α and IL-8 were noticed to be declined in women who had T. vaginalis infection, although they were not declined significantly. This study gives an insight about some clinical aspects of T. vaginalis infection among PID women. T. vaginalis is highly predictable in women with PID. Consequently, attention and more investigation would be needed on this topic in Iraq.